Efficacy of Liquid Waste Reduction using Anaerobic and Aerobic Median Biofilters in Tofu Factory X, Pematang Sulur, Jambi City - Lailal Gusri; Karenina Juniska; Tri Syukria Putra (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2025)
Tofu is a popular soy-based food. Tofu manufacturing produces wastewater that can pollute the environment, and waste discharged into rivers must meet wastewater quality standards. Wastewater treatment can increase factory operating costs. The purpose of this study was to determine the effectiveness of reducing Tofu Factory X's wastewater parameters, namely BOD, COD, TSS, and pH. Research Methods 1) observation and data collection on water discharge for daily manufacturing operations, 2) calculation of equalization basin plan, anaerobic and aerobic biofilters, oxygen requirements and blowers, 3) raw water and wastewater quality testing from the design of the wastewater treatment plant of Tofu Factory X, and 4) calculation of the reduction efficiency of BOD, COD, TSS and pH and comparison with the Minister of Environment Regulation No. 5 of 2014. The research results obtained showed the reduction efficiency of BOD pollution by 30.75%, COD by 35%, TSS by 68.08% and pH by 4.55. The wastewater treatment in this study did not fully demonstrate the expected efficiency, as adjustments had to be made to the required air quantity, temperature, and residence time. Keywords: anaerobic and aerobic, biofilter, liquid waste, tofu factory, wastewater quality.